Penyuluhan Pembuatan Dodol Kolang-Kaling di Kecamatan Gedong Tataan Kabupaten Pesawaran - Kholifah, Nurul; Apriana , Dwi; Manova , Eka Widia Arta (Jurnal Pemberdayaan Ekonomi, 2024)
Purpose: This study aims to enhance the income of housewives through kolang-kaling dodol production training. Methodology/approach: The kolang-kaling dodol training was held in Gedong Tataan Subdistrict, Pesawaran Regency, and involved housewives from the local PKK community group. The training aimed to improve their skills in processing kolang-kaling into a valuable product to help increase household income. It also encouraged creativity in utilizing local resources. Results/findings: The dodol kolang-kaling production training in Gedong Tataan District received a positive response from PKK housewife members, with 8 out of 12 participants actively taking part in the activity. The participants showed great enthusiasm in learning about processing, packaging, and the potential market value of dodol kolang-kaling as a healthy and economically valuable food product. Conclusion: The dodol kolang-kaling production training held in Gedong Tataan District, Pesawaran Regency, successfully enhanced the knowledge, skills, and entrepreneurial spirit of housewives who are members of the PKK. Through this training, participants not only acquired technical skills in processing and packaging products, but also gained an understanding of the economic potential of kolang-kaling as a healthy and marketable alternative food ingredient. Limitations: The limited number of active participants only 8 out of 12 PKK members was one of the constraints in this training. This was due to some participants having other work obligations as educators, preventing them from fully engaging in the entire training session. Contribution: This training contributed to enhancing household economic resilience by equipping participants with practical skills and entrepreneurial insight through the utilization of local food resources.